Wisdom and Justice from a Traditional, Artisanal Towards an Applied Scientific Justice - Vandamme, Fernard; Muylle, Filip (Տիգրան Մեծ)
Wisdom in its different forms is strongly related to the harmonic use of the different types of intelligence. Wisdom we can observe even on the micro-level of the organism. On the community-macro level the need and the use of wisdom is more clearly present. Nevertheless the wisdom on the micro level is a very interesting heuristic tool too as a metaphor for better understanding the function, use and challenges of wisdom at the community level. Traditionally Justice is an important domain of application of wisdom. Today this is even more true than ever. The implications for surpassing the artisanal in favour of an Applied Scientific Justice are here really challenging.
Keywords: Social philosophy